2019
DOI: 10.3892/ijo.2019.4882
|View full text |Cite
|
Sign up to set email alerts
|

Genome profiling revealed the activation of IL2RG/JAK3/STAT5 in peripheral T‑cell lymphoma expressing the ITK‑SYK fusion gene

Abstract: Peripheral T-cell lymphomas (PTCLs) are heterogeneous malignancies that are types of non-Hodgkin lymphomas; patients with this disease have poor prognoses. The IL-2-inducible T-cell kinase-spleen tyrosine kinase (ITK-SYK) fusion gene, the first recurrent chromosome translocation in PTCL-not otherwise specified (NOS), can drive cellular transformation and the development of T-cell lymphoma in mouse models. The aim of the current study was to investigate the signal transduction pathways downstream of ITK-SYK. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“… 22 , 23 , 24 , 25 Comparable results are observed with Non‐Hodgkin's lymphoma, in which activation of IL2Rγ—JAK3—STAT5 signaling pathway significantly promotes cancer progression while knockdown of IL2Rγ garners the same effect as Tofacitinib, a JAK inhibitor that effectively inhibits the activity of JAK1 and JAK3. 26 , 27 Actually, Julianna Volkó et al found the assembly of IL2R may occur and exert its function in the cytoplasm, which is a probable factor in immunotherapy resistance, 28 as IL2Rβ and IL2Rγ could form ligand‐independent homodimerization and stimulate mutant JAK3‐STAT pathway. 29 However, there still exist no reports on whether IL2RG is abnormally expressed and what influence ectopic IL2RG expression levels may exert in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 , 24 , 25 Comparable results are observed with Non‐Hodgkin's lymphoma, in which activation of IL2Rγ—JAK3—STAT5 signaling pathway significantly promotes cancer progression while knockdown of IL2Rγ garners the same effect as Tofacitinib, a JAK inhibitor that effectively inhibits the activity of JAK1 and JAK3. 26 , 27 Actually, Julianna Volkó et al found the assembly of IL2R may occur and exert its function in the cytoplasm, which is a probable factor in immunotherapy resistance, 28 as IL2Rβ and IL2Rγ could form ligand‐independent homodimerization and stimulate mutant JAK3‐STAT pathway. 29 However, there still exist no reports on whether IL2RG is abnormally expressed and what influence ectopic IL2RG expression levels may exert in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…In PTCL, as mentioned above, the JAK3/STAT5 signaling program was identified to be downstream of ITK/SYK via Signal Net and cluster analyses of microarray data. JAK3 selective inhibitor tofacitinib abrogated the phosphorylation of STAT5, suppressed cell growth, induced cell apoptosis and arrested the cell cycle at the G1/S phase [5]. As JAK3-activating mutation was frequent in NKTCL pathogenesis, the pan-JAK inhibitor Tofacitinib efficiently reduced phosphorylated STAT5 and cell viability in JAK3-mutant and wild-type NKTCL cell lines and mouse xenografts [19,24].…”
Section: Monotherapymentioning
confidence: 97%
“…A double kinase fusion ITK-SYK was identified in PTLC, which drove cellular transformation and progression of this malignancy. Additionally, through microarray data analysis, JAK3/STAT5 activation was discovered as a downstream effect of ITK-SYK aberrance, and pharmacological inhibition of JAK3 abrogated STAT5 phosphorylation, suppressed cell survival and induced G1/S phase arrest [5].…”
Section: Upstream Drivers For Jak Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the cases with ITK-SYK were later confirmed as Tfh like-PTCL [ 55 ]. ITK-SYK proteins were demonstrated in Jurkat cells to activate the IL2RG/JAK3/STAT5 signaling pathway, which was associated with the abundant secretion of IL-2 and IL-21 [ 56 ]. In a mouse model of ITK-SYK induced T-cell lymphoma, ITK-SYK was found to enhance the expression of PD-1 that subsequently attenuated the AKT and PKC activities in premalignant ITK-SYK expressing cells [ 57 ].…”
Section: Activating Mutations In Genes Related To Tcr Signaling In Ptclsmentioning
confidence: 99%